Preparation and characterization of hybrid organic−inorganic nano composite coating / Ammar Shafaamri - Shafaamri, Ammar (2015)

(untitled)
The objective of the present work is to develop organic-inorganic nanocomposite coatings based on epoxy resin and hydroxyl-terminated polydimethylsiloxane (PDMS). The developed PDMS-epoxy polymeric matrix was used as the host for various weight percentages of reinforcement nanoparticles namely SiO2 and ZnO. The employment of organic and inorganic functionalities into a single coating system provides a unique combination of distinctive properties. In this work, embedding nano-sized particles within the polymer matrix was carried out by utilizing the solution intercalation method. After that, the influence of the nanoparticles in enhancing the overall anticorrosion performance and the hydrophobicity properties were investigated. The electrochemical, thermal, structural and wettability properties of PDMS-epoxy nanocomposites have been examined. The results showed that that the coating system with 2 wt.% SiO2 exhibited the most pronounced improvement. Same observation was related to the system reinforced with 2 wt.% ZnO nanoparticles. Superior corrosion resistance (Rc) with approximately 1 x 1011 Ω after 30 days of immersion in 3% NaCl solution was recorded. Nanocomposite coatings with hydrophobic characters were successfully achieved by increasing the surface roughness of the coated sample. Furthermore, the thermal studies of the archived systems reveal a good influence of the nanoparticles within the binder with no significant effects on the glass transition temperature.